Neutrosophic Perspectives in Healthcare Decision-Making: Navigating Complexity with Ethics, Information, and Collaboration - Alex Gabriel Lara Jacome; Elizabeth Mayorga Aldaz; Miguel Ramos Argilagos; Darvin Manuel Ramírez Guerra (Neutrosophic Sets and Systems, 2023)
Decision-making in healthcare is a multifaceted process that involves multiple actors and factors. It is a crucial process that directly influences the quality of care provided to patients. To make appropriate clinical decisions, it is essential to have accurate clinical information, including medical histories and test results, in addition to considering ethical principles. Interdisciplinary consultation, proper documentation, and institutional policies play a vital role in ethical and clinical decision-making, especially in complex situations. Research utilizes methods such as COPRAS and neutrosophic correlation coefficients to guide decision-making in complex situations, but it is emphasized that results may vary depending on the method used and the subjectivity of experts. The results highlight the importance of ethical principles in clinical decision-making, including doing good, avoiding harm, treating all patients fairly, and respecting patient autonomy. The combination of clinical information, ethical principles, and active participation of patients and their families is essential for making informed and ethical decisions that promote the health and well-being of patients.